Unity in Diversity: The case of FCC - CUSROW J. DUBASH; UMAIR JAMAL (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This paper aims to shed light on the question, "How did FC College’s missionary college status present a unique challenge for the institution between 1973 and 2002, and how did the institute recover its enduring legacy of national unity?" In addition, the study intends to provide a high-level overview of how FC College has attempted to accomplish all this by referencing specific cases involving two or more racial/ethnic student groups that are well-known for their contentious interactions on campus.Method: The research methodology employed in this study is primarily descriptive and analytical in nature,covering topics such as the institute’s history, the radical changes brought about by several state policies, and the various efforts put forth by the university’s administration to restore the institute to its former academic glory.Findings: The case of the FCC demonstrates that there is still a functional mechanism to involve the wide range of competing interests and identities that permeate modern society and the institutional milieu in which academia operates. The politicisation of universities can be avoided if a method is introduced that firmly emphasises the liberal and progressive side of all competing interests.Implications/Novel Contribution: This research is significant because it sheds light on a promising approach taken by some educational institutions, namely that fostering a welcoming and inclusive learning environment that encourages students to explore their passions and develop their talents can also help reduce tensions between different groups based on race and ideology. While this is just one example, identity-based tensions persist at all Pakistani universities.